ASSESSMENT OF A COMMUNITY: PROMOTING AN EQUITABLE SOCIETY THROUGH INCLUSION AND EMPOWERMENT - Nel, Hanna; Roestenburg, Wim (Social Work/Maatskaplike Werk, 2004)
To adhere to the new developmental welfare policy of South Africa, the Department of Social Work at the Rand Afrikaans University (South Africa) in co-operation with the African Self-Help Association (ASHA), a non-profit organisation, conducted a needs assessment for Soweto among all the families connected with the 40 preschool crèches of ASHA. Findings from participatory action research indicated a need for four different programmes: programmes for preschool children; programmes to enhance community leadership; family enrichment programmes; and special delivery programmes regarding HIV/AIDS, disability, crime and violence, illiteracy, poverty alleviation and substance abuse. Through the principle of inclusion, people took ownership of these programmes, which in turn had an empowering effect on them.